Study of adsorbent characteristics of palm leaves powder as a bio sorbent for removal of malachite green (MG) dye. (2022) - Malhotra, Anu; Srivastava, Sonia; Manjhu, Suchitra; Lokhande, Rama S; Sahu, Rajesh; Jain, S.K.; Sharma, K.B.; Tripathi, Balram
Highlights: Bio adsorbent. Degradation of dye. Photocatalytic adsorption. Stability of adsorbent for removal of dyes. The novelty of present work shows the role of palm leaves waste for the best. Abstract: Palm leaves were used as the bio sorbent in an adsorption uptake study to remove malachite green (MG). MG is a water-soluble cationic dye that looks as a green crystalline powder and is classified as a triphenylmethane. FE-SEM, FT-IR, and UV–vis absorption spectroscopy were used to examine the palm leaves. Using optical absorption spectroscopy, the influence of various factors such as time, initial dye concentration, colour discharged dilution, pH, and amount of bio sorbent on dye removal percentage was investigated. It was discovered that the dye removal rate increased with increasing pH but decreased in acidic medium.